Humic substrates application in diluted form enhanced availability of phosphorus (P) and its uptake by tea bushes in the tea-growing soil of Northeast India. (14th December 2017) - Pramanik, Prabhat; Safique, Shamina; Jahan, Asrafa; Bhagat, Rajib M.
ABSTRACT: Tea ( Camellia sinensis L.) is an evergreen perennial crop, which is cultivated for its shoots in acidic soil under sub-tropical humid climatic condition. The availability of phosphorus (P) to plants is naturally limited in acidic tea-growing soils. Humic substrates (HS) are often applied to enhance availability of nutrients, especially P in horticultural and vegetable crop fields. However, its effect on soil of a perennial crop like tea was not studied before. In this study, application of HS enhanced P availability mainly by facilitating growth of phosphate-solubilizing bacteria (PSB) and enhancing phosphatase activity in soil. Application of same amount of HS in diluted form was more effective to enhance PSB population and phosphatase activity, which in turn increased P availability in soil and P uptake by tea bushes. This experiment indicated that application of 1.5 kg HS ha −1 as 0.3% solution might be applied to enhance P availability to improve P availability and P uptake by plants in tea-growing soil.